Efektywność gospodarstw mlecznych w Polsce i Niemczech w latach 1992 i 1994 - Bereżnicka, Joanna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1998)
In the face of Poland's membership of the European Union the key problem constitutes the production factors management. In the paper there was presented an analysis of making use of land, labour and capital by Polish and German dairy farms. lnformation is based on data of agricultural holdings keeping books in 1992 and 1994. The analysis shows that Polish fanners compared with the German operate on threefold less acreage and have in stock fivefold lower number of cows. Average productivity of animals in Polish ag1icultural holdings reaches 30 - 40 per cent of milk yield per 1 cow in Germany. Above mentioned factors basically determine low output value (low unity efficiency). Generated farm. income per farmland unit and per labour unit in German holdings is considerably higher in comparison with Polish farms. Generally, Polish farms achieved significantly lower efficiency of principal production factors in agriculture.